Auf dem Weg zur schmerzarmen Kinderklinik: Nutzung von EMLA in neuropädiatrischen Einrichtungen der deutschsprachigen Länder - Perry, Diana; Ebinger, Friedrich (Monatsschrift Kinderheilkunde, 2012)
Avoiding or reducing the pain experienced by inpatient children and adolescents during medical procedures is an issue of growing importance. To what extent the daily clinical routine has changed is unclear. In order to ascertain this we developed a six-page questionnaire and sent it to 424 facilities in Germany, 49 in Austria and nine in German-speaking Switzerland that carry out neuropaediatric procedures.We also contacted so-called social paediatric centres in Germany. The enquiry period was from June 2008 to January 2009. The return rate was 54% (Germany 55%, Austria 40%, Switzerland 66%). We found clear differences in the handling of painful procedures between the different countries as well as between various facilities. While in Switzerland and Austria use of EMLA (eutectic mixture of local anesthetics) is routine for taking blood samples or venous catheter insertion, and in Austria also for lumbar puncture, only a quarter of all facilities in Germany use EMLA cream “often” or “routinely” for blood tests, whereby its use largely depends on the physician in charge, especially at university clinics. Nevertheless, German physicians appear to be unsatisfied with the current status of EMLA usage. In all, 60% of the doctors surveyed at university clinics would prefer to see more frequent use of EMLA cream for their patients.Three quarters of the responding clinics use local anaesthesia “almost always” or “often” for lumbar puncture. The ratio increases significantly if the clinic has guidelines for pain management in place. The recommended EMLA application time of 60 min is adhered to by less than one-fifth of German physicians.